Hubungan Pengetahuan dan Sikap terhadap Pemberian Terapi Insulin dalam Situasi Non-Critical Pasien Diabetes Melitus - Abd Gani Baeda (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Diabetes mellitus is a chronic metabolic disorder disease caused by ineffective production of insulin used by the body causing hyperglycemia. Blood sugar is controlled by insulin. One of the therapy in control of blood sugar is insulin. The aim of this study was to find out the correlation among nurses knowledge, attitudes and behaviors in handling and administering insulin. A Cross-sectional design study involving 103 nurses in the surgery and internal room applied to this study. The results showed that there was no significant correlation between knowledge and attitudes toward nurses' behavior in providing noncritical insulin therapy. A majority of respondents have 67% moderate knowledge, 50% of respondents have a positive attitude, and 61.2% of respondents have satisfactory behaviour. The Conclusion of this study was the training is required to improve knowledge and satisfactory performance.